Development of Virtual Reality–Based Learning Media on Particle Motion Dynamics Using the Kuula Platform Supported by a Digital Flipbook to Improve Conceptual Understanding of Senior High School Grade XI Students - Putri Wiji Rahayu; Eko Risdianto; Andik Purwanto; M. Abdul Jamal (CV. Media Inti Teknologi, 2026)
Background: Innovative learning media are needed to address students’ difficulties in understanding abstract physics concepts, particularly Particle Motion Dynamics, especially in schools with limited laboratory facilities.Aims: This study aimed to develop Virtual Reality (VR) learning media based on 360° videos using the Kuula platform supported by a digital flipbook and to examine its validity, practicality, and effectiveness in improving senior high school students’ conceptual understanding.Methods: This study used a Research and Development (R&D) approach with the ADDIE model. The effectiveness of the product was tested using a one-group pretest–posttest design involving 40 Grade XI students at SMA Negeri 4 Bengkulu City. The product was validated by two physics lecturers and one physics teacher. Data were collected using validation sheets, student response questionnaires, and a conceptual understanding test. Data analysis included the Shapiro–Wilk test for normality, followed by the Wilcoxon signed-rank test to determine differences between pretest and posttest scores. Effect size was also calculated to measure the magnitude of the treatment effect.Results: Expert validation showed an average feasibility score of 97, categorized as “very feasible”. Students’ responses were highly positive, with a score of 97 (“very good”). The N-Gain analysis indicated a significant improvement in conceptual understanding, with the average score increasing from 29 (pretest) to 93 (posttest), categorized as high improvement.Conclusion: The Kuula platform–based VR learning media supported by a digital flipbook was valid, received positive responses from students, and effectively improved students’ conceptual understanding of Particle Motion Dynamics. Therefore, it is feasible to be used as an alternative medium for physics learning.